Community-Based Landslide Disaster Mitigation: Integrating Local Knowledge for Strengthening Community Resilience: A Qualitative Study on Community Participation and Disaster Risk Reduction - Dwiki Hermawan; Mohammad Ikhwan Syahtaria; Dody Ruswandi (Cita konsultindo, 2026)
Landslides represent a significant natural hazard, particularly in regions characterized by steep topography and high rainfall intensity. In Indonesia, landslides frequently occur due to a combination of natural and anthropogenic factors, resulting in severe socio-economic and environmental impacts. Conventional disaster mitigation approaches, which are often top-down in nature, have not been fully effective in enhancing community resilience. This study aims to analyze the role of community-based approaches in landslide disaster mitigation through the integration of local knowledge and capacity strengthening.This research employs a qualitative approach using a descriptive method, with data collected through an extensive literature review of academic journals, books, and official reports. The findings indicate that local knowledge plays a crucial role in identifying early warning signs of landslides, managing environmental conditions, and supporting traditional mitigation practices. Furthermore, the community-based approach enhances participation, strengthens local ownership, and improves the sustainability of disaster risk reduction efforts.The integration of local knowledge with scientific approaches provides a more comprehensive and adaptive mitigation framework, contributing to improved community resilience. Therefore, effective disaster mitigation requires strong collaboration among communities, governments, and other stakeholders to develop inclusive, context-specific, and sustainable strategies. This study contributes to the growing body of knowledge on community-based disaster risk reduction by emphasizing the importance of integrating local knowledge into formal disaster management frameworks.